Comparison of the growth of males and females of tilapia Oreochromis Niloticus cultured in cages - Alvarado-Ruiz, Carlos (2015)
With the purpose of evaluating productive performance and potential weight gain capacity of snapper O. Niloticus without reversing, we evaluated the growth of males and females raised in floating cages in captivity grouped by gender. The experiment was conducted for a term of 150 days.  We used a simple 4 836 alevins of 26.2±19.7g, fish that were nourished until they visibly reached sexual differentiation to 119.3±56.5 g to be separated by sex and nourished in floating cages to a final average weight of 387.0±128.9g (harvest)to determine differences in growth. The weight distribution of the undefined gender sample showed a decrease in the coefficient of variation (CV) of 75.13% to 31.49 and 30.22 for males and females respectively. This indicates that the distribution of sizes of the samples tended to become normal during the cycle of harvest. Significant differences (P=0.05) for the weight of harvest 429.2±135.1g and 339.65±102.64 g.   For the growth rate 2.74±0.86g day y 2.18±0.68 g day were determined between males and females respectively. The standard error of the estimation of the difference of average weight between males and females was 89.62±7.23g for an accuracy level of 95%. Males displayed  better growth rate and weight gain for harvest.